Best paper, Conference - Loizou, Christos P. (My University, 2026)
T. Greiner, C.P. Loizou, M. Pandit, J. Mauruschat, F.W. Albert, “Speckle reduction in ultrasound imaging for medical applications,” Proc. of the ICASSP 91-1991 Int. Conf. Acoustic Speech & Sign. Proces. Toronto, Canada, pp. 2993-2996, May 14-17, 1991.
Keywords: Sciences